1999
DOI: 10.1136/jnnp.66.2.137
|View full text |Cite
|
Sign up to set email alerts
|

The cholinergic hypothesis of Alzheimer's disease: a review of progress

Abstract: Alzheimer's disease is one of the most common causes of mental deterioration in elderly people, accounting for around 50%-60% of the overall cases of dementia among persons over 65 years of age. The past two decades have witnessed a considerable research eVort directed towards discovering the cause of Alzheimer's disease with the ultimate hope of developing safe and eVective pharmacological treatments. This article examines the existing scientific applicability of the original cholinergic hypothesis of Alzheim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

17
1,161
1
37

Year Published

2003
2003
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 1,863 publications
(1,216 citation statements)
references
References 102 publications
17
1,161
1
37
Order By: Relevance
“…A number of studies have demonstrated that vestibular stimulation can improve cognition in humans (reviewed in [91][92][93]). Given that synaptic plasticity is altered in patients with Alzheimer's disease [94] and degeneration of basal forebrain cholinergic neurons is a pathological hallmark of this disease [14,15,95,96], vestibular stimulation may provide a novel treatment to improve hippocampus-dependent cognitive deficits in affected patients.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A number of studies have demonstrated that vestibular stimulation can improve cognition in humans (reviewed in [91][92][93]). Given that synaptic plasticity is altered in patients with Alzheimer's disease [94] and degeneration of basal forebrain cholinergic neurons is a pathological hallmark of this disease [14,15,95,96], vestibular stimulation may provide a novel treatment to improve hippocampus-dependent cognitive deficits in affected patients.…”
Section: Resultsmentioning
confidence: 99%
“…However, a few experiments in which a short (<15 s) afterdischarge was evoked were included, since the magnitude of LTP (expressed at a ratio of the baseline) was similar to experiments without afterdischarge [42]. Following tetanus, AEPs were recorded at "fixed" times at 5,10,15,20,30,60,90,120,150 and 180 min. Previous data showed that LTP magnitude was not significantly different among test pulses of 1.5-2× fEPSP threshold intensity [43]; therefore, all AEPs were recorded with test pulse of 1.5× the fEPSP threshold.…”
Section: Recording and Analysis Of Evoked Potentials And Eegmentioning
confidence: 99%
See 1 more Smart Citation
“…In human volunteers, the pattern of cognitive impairment caused by scopolamine mimics in some aspects the cognitive symptomology seen in Alzheimer's disease (AD) (Ebert and Kirch, 1998) which is associated with the degeneration of cholinergic neurons in the basal forebrain resulting in a reduction of cholinergic neurotransmission in the forebrain (Araujo et al, 1988;DeKosky et al, 1996;Kuhl et al, 1999;Shinotoh et al, 2000;Shiozaki et al, 1999;Whitehouse et al, 1982). On the other hand, acetylcholinesterase (AChE) inhibitors, which increase synaptic acetylcholine (ACh) levels, are effective in the treatment of some cognitive symptoms of AD (Francis et al, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…In addition to a deficit in cholinergic transmission, dementia is also related to degeneration of glutamatergic hippocampal and cortical pyramidal neurons (Aronica et al, 1998;Francis et al, 1999), which are targets for cholinergic and serotonergic innervation. Furthermore, the activity of glutamatergic neurons in the hippocampus and neocortex is modulated by cholinergic systems, which have facilitatory effects mediated via muscarinic receptors (Cole and Nicoll, 1984;Segal, 1982), and serotonergic systems, which have inhibitory effects partly mediated via 5-HT 1A receptors (Beck et al, 1992;Davies et al, 1987;Newberry et al, 1999;Pugliese et al, 1998).…”
Section: Introductionmentioning
confidence: 99%